The comparison of problem solving skills of post graduate students in teacher's colleges in terms of their levels - (:unkn) unknown (ANI YAYINCILIK, 2007)
Problem Statement: The characteristics of the people having 'Problem Solving Skills' have been observed and as the result of the researches, it has been found that those people have self esteem and creative thinking by means of an objective point of view. Besides they have the abilities of being impulsive without worrying too much about the cases they have comforted with. It is concluded that all would be teachers must carry these features. Thus researches had to be conducted on the subject of would be teachers finding themselves competent in solving the problems they confront with and their perceptions. Purpose: The differences between the levels of perception in problem solving skills of post graduate students in Music Education Department and Psychological Counseling and Guidance Departments have been analyzed in this research. Due to these reasons, the perception levels of two student groups in problem solving skills have been analyzed under several variables. Methods: The Survey Methodology has been used in this research. 162 people who are teachers in GSEB Music Education (N=92) and Psychological Counseling and Guidance Departments (N=70) in 2006-2007 Academic Year. The data in research has been collected by 'Individual Information Form' for students and 'Problem Solving Inventory' Form-A (PSI-A) developed by P.P Heppner and C. H. Petersen in 1982. The information and data collected have been analyzed by using frequency distribution, Kruskal Walls and Mann-Witney U test in SPSS package program. Findings and Results: As the result of the analysis of data, it has been concluded that the levels of perception of students in Psychological Counseling and Guidance Departments are lower compared to the levels of perception of students in Music Education Department. The points which the students in Physiological Counseling and Guidance Departments have got in Approaching-Avoidance (AA) and Personal Control (PC) sub scales have been found to be less inadequate compared which was an unexpected result in the aspect of the education they have. Recommendations: Considering the fact that every educationalist must have problem solving skills, researches in detail have to be conducted in detail on various factors which may affect this skill.
Keywords: problem solving skills; teacher education; psychological counseling and guidance; music education